2008
DOI: 10.1108/08880450810898283
|View full text |Cite
|
Sign up to set email alerts
|

An exponential smoothing model for predicting traffic in the library and at the reference desk

Abstract: PurposeThe purpose of this study is to develop a mathematical model that can be used to forecast the number of individuals who enter the library as well as the number of patrons that seek assistance at the reference desk of the library. An accurate estimate of demand at the reference desk is valuable for effective staffing decisions.Design/methodology/approachAn exponential smoothing model (Winter's model) was developed for forecasting. Data were gathered at the University of Tennessee at Chattanooga for an en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Using survey data from 182 library building projects, Shill and Tonner concluded that "in general, building improvements had a greater overall impact on basic facility use (gate count) than on circulation, reference, transaction volume, and in-house collection use" (2004, p. 127). Other researchers have offered predictive models for calculating reference transactions based off gate counts and occupancy rates (Ahmadi, Dileepan, & Murgai, 2012;Ahmadi, Dileepan, Murgai, & Roth, 2008;Murgai & Ahmadi, 2007), but as none of the studies have considered the large spike in traffic associated with opening a learning commons, it is uncertain how applicable these models would be for libraries with these spaces.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Using survey data from 182 library building projects, Shill and Tonner concluded that "in general, building improvements had a greater overall impact on basic facility use (gate count) than on circulation, reference, transaction volume, and in-house collection use" (2004, p. 127). Other researchers have offered predictive models for calculating reference transactions based off gate counts and occupancy rates (Ahmadi, Dileepan, & Murgai, 2012;Ahmadi, Dileepan, Murgai, & Roth, 2008;Murgai & Ahmadi, 2007), but as none of the studies have considered the large spike in traffic associated with opening a learning commons, it is uncertain how applicable these models would be for libraries with these spaces.…”
Section: Review Of Literaturementioning
confidence: 99%
“…A variety of quantitative and statistical methods have been applied to evaluate different aspects of reference services. Major topics considered include staffing needs (Murgai, 2006;Ryan, 2008;Applegate, 2008) and forecasting reference desk traffic flows (Murgai and Ahmadi, 2007;Ahmadi et al, 2008;Dubnjakovic, 2012). Statistical methods used in these studies include comparisons of means (Ryan, 2008), chi-squared residual analysis (Murgai, 2006;Applegate, 2008), multivariate regressions (Murgai and Ahmadi, 2007;Dubnjakovic, 2012) and time series analysis (Ahmadi et al, 2008).…”
Section: Methodology For Reference Assessmentmentioning
confidence: 99%
“…Yet, to our knowledge, no quantitative study has been conducted so far to investigate the possible impact brought by a new reference tool, such as online chat, on the traditional face-to-face reference services. Ryan, 2008), chi-squared residual analysis (e.g., Murgai, 2006;Applegate, 2008), multivariate regressions (e.g., Murgai and Ahmadi, 2007;Dubnjakovic, 2012), and time series analysis (e.g., Ahmadi et al, 2008). Although in-depth qualitative assessment has been adopted in much of the existing research on chat reference, quantitative analysis of chat volume in academic libraries with statistical methods employed in other reference fields has rarely been conducted.…”
mentioning
confidence: 99%
“…Mathematical forecasting models have been used for forecasting numerous variables in libraries. For instance, a multiple regression has been used to successfully predict the reference desk staffing requirements (Murgai and Ahmadi, 2007), and an exponential smoothing model was used to predict traffic in the library and at the reference desk (Ahmadi et al, 2008). In the current study, a Centered Moving Average with seasonal variation model was formulated for forecasting the demand for ILL.…”
Section: Introductionmentioning
confidence: 99%